Tracing the autobiographical - Kadar, Marlene, 1950- (Wilfrid Laurier University Press, 2005)
Annotation Essays analyze the autobiographical impulse in variety of contexts, genres, and locations to reveal the intersections of personal revelation with vital modern and historical events.
Keywords: Autobiography.; Autobiography in literature.; Autobiographies as Topic; Autobiographie dans la littérature.; Autobiographie.; autobiography (genre); TRAVEL -- Special Interest -- Literary.; LITERARY CRITICISM -- General.; Autobiography in literature; Autobiography; Autobiografie; Autobiografieën.